Hauora hinengaro o takatāpui: analysing the effectiveness of mental health policies in addressing the needs of Takatāpui in Aotearoa New Zealand - Benvie-Watson, Emma; Greaves, Lara M. (Culture, Health & Sexuality, 2024)
Many studies have documented the effect that colonisation has had on takatāpui, that is, Māori (the Indigenous peoples of New Zealand) with diverse gender identities, sex characteristics and sexualities. In this paper, we explore whether current Aotearoa New Zealand (hereafter Aotearoa) mental health policies meet the needs of takatāpui. We identified five mental health policy needs, informed by the literature. We then explored policy documents from government ministries, district health boards and non-government organisations to see the extent to which policy met these needs. Four themes were present in the literature analysed: an overall lack of acknowledgment of takatāpui and intersectionality; promising engagement with the needs of takatāpui by NGOs; symbolic commitment to Te Tiriti o Waitangi; and some limited engagement with Māori health models. The findings show promise in some areas but demonstrate a lack of engagement by policy to meet the needs of takatāpui.
Keywords: Identity & Intersectionality; Mental health; Māori; Policy; Takatāpui

Indigenous Representational Choices: Results from a Large Qualitative Survey on Māori Electoral Roll Choice - Greaves, Lara Marie; Hini, Rebecca; Overbye, Hannah R.; Brink, Kaylee Grace (Journal of Race, Ethnicity, and Politics, 2025)
Different participatory mechanisms for the representation of Indigenous peoples have been proposed across states. Since their creation in 1867, the Māori electorates in the national Parliament have led to dedicated representation for Māori (Indigenous peoples of New Zealand). However, only half of Māori choose to vote on the Māori roll, the remainder choosing to vote on the General roll, illustrating that roll choice is not based simply on group representation. This survey aimed to ask Māori (N = 1,958) in their own words why they made their roll choice. Through a deductive codebook thematic analysis, a range of codes were constructed around the reasoning behind roll choice. Māori on the Māori roll made their choice because they valued Māori representation; as an expression of their identity; to support the electorates; as a strategic choice; or they had been influenced by others or through education. Those on the General roll felt their roll was the default or a more familiar option; the Māori roll had less of an impact; it was a strategic choice, or they appreciated greater candidate variety; or they valued the smaller geographic electorate size. Some felt Māori no longer needed separate representation or felt less connected to their identity as Māori. The results have implications for both Māori and Indigenous representation through dedicated representational mechanisms.
Keywords: Indigenous; Māori; Māori electorates; Voting; Parties; Parliament; representation; voter enrolment